DEVELOPING STUDENTS' ENGLISH WRITING SKILLS: PROBLEMS, METHODS, AND PROSPECTS - Abdiganiyeva Gozalxon Oxunjon kizi (Bright Mind Publishing, 2025)
This article addresses the major challenges faced by university students in developing English writing skills and suggests effective pedagogical methods to overcome them. The study highlights the importance of step-by-step writing, reflective learning, and peer review as essential strategies for improving writing quality. It aims to integrate theoretical and practical aspects to enhance the effectiveness of English language teaching.
Keywords: Writing skills, methodology, students.